The Impact of Artificial Intelligence (AI) Technology Usage on English Skills Among Thai High School Students - Monica Sitorus, Fenna; Jamaluddin Nasution; Lisa Septia Dewi Br. Ginting (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to examine the effect of rule-based artificial intelligence (AI) applications, such as Duolingo, Grammarly, Babbel, and ELSA Speak, on the English language proficiency of Thai high school students. Using a sequential explanatory mixed-methods design, data were collected through questionnaires and in-depth interviews with 30 purposively selected students who actively used AI-based language learning tools. The quantitative findings show that AI usage has a significant yet limited impact, explaining 13.8% of the variance in students’ English-speaking ability. Qualitative results revealed that students perceived AI applications as helpful for improving grammar and pronunciation, though less effective for complex language tasks requiring contextual understanding. Although the sample size restricts generalizability, this study highlights the potential of AI as a complementary tool in English learning and underscores the importance of aligning AI use with pedagogical strategies suited to the Thai educational and cultural context.